Alcohol consumption during adolescence alters the hippocampal response to traumatic brain injury - Mira, Rodrigo G.; Lira, Matias; Quintanilla, Rodrigo A.; Cerpa, Waldo (My University, 2020)
Binge drinking is the consumption of large volumes of alcohol in short periods and exerts its effects on the central nervous system, including the hippocampus. We have previously shown that binge drinking alters mitochondrial dynamics and induces neuroinflammation in the hippocampus of adolescent rats. Mild traumatic brain injury (mTBI), is regularly linked to alcohol consumption and share mechanisms of brain damage. In this context, we hypothesized that adolescent binge drinking could prime the development of brain damage generated by mTBI. We found that alcohol binge drinking induced by the "drinking in the dark" (DID) paradigm increases oxidative damage and astrocyte activation in the hippocampus of adolescent mice. Interestingly, adolescent animals submitted to DID showed decreased levels of mitofusin 2 that controls mitochondrial dynamics. When mTBI was evaluated as a second challenge, hippocampi from animals previously submitted to DID showed a reduction in dendritic spine number and a different spine profile. Mitochondrial performance could be compromised by alterations in mitochondrial fission in DID-mTBI animals. These data suggest that adolescent alcohol consumption can modify the progression of mTBI pathophysiology. We propose that mitochondrial impairment and oxidative damage could act as priming factors, modifying predisposition against mTBI effects. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: alcohol; traumatic brain injury; oxidative stress; mitochondria; dendritic spine